Effectiveness of Trauma-Focused Cognitive-Behavioral Therapy on the Grief Symptoms and Behavioral Problems of Bereaved Children (One-Month Follow-Up) - Gelareh Rezaei Kangarshahi; Masoud Shahbazi; Amin Koraei; Seyedeh Zahra Alavi (پژوهش‌های کاربردی روانشناختی, 2023)
The purpose of the present study was to investigate the effectiveness of trauma-focused cognitive-behavioral therapy on the bereavement symptoms and behavioral problems of grieving children. In this investigation, a single-case experimental design with incongruent multiple baseline designs was used. The statistical population of the present research was comprised of bereaved children in the city of Karaj who have lost a parent within the past six months. The investigation was conducted between January and May of 2021. The research sample consisted of three minors aged 10 to 11 who were selected using a method of purposive sampling based on the inclusion criteria. During two and a half months, the experimental group received ten 75-minute sessions of trauma-focused cognitive-behavioral therapy. This study utilized the Children’s Grief Questionnaire (CGQ) and the Child Cehavior Checklist (CBCL) as questionnaires. The study’s data were analyzed using the statistical software SPSS-22, visual representation, the dynamic change index, and the improvement percentage formula. The degree of improvement in the variable of grief was 34, 27.53, and 29 for the first, second, and third subjects, respectively, and the calculated dynamic change index was 3.18, 3.56, and 3.14. Moreover, the degree of improvement in the variable of internalized behavioral problems was 46.66, 31.50, and 38.02 for the first, second, and third subjects, respectively, and the calculated dynamic change index was 2.07, 2.96, and 2.14. In addition, the degree of externalized behavioral disorders was 46.98, 40.82, and 45.92 for the first, second, and third subjects, respectively, and the calculated dynamic change index was 2.34, 2.02, and 1.98. After treatment, the amount of dynamic change index was greater than Z (1.96); the results of this study suggest that cognitive-behavioral therapy is an effective method for reducing the bereavement and behavioral problems of grieving children.